A critical role for HER3 in HER2-amplified and non-amplified breast cancers: function of a kinase-dead RTK - Dey, Nandini (Am J Transl Res, 2015)
ERBB3/HER3 is the most intriguing RTK by virtue of its ability to transduce multiple cytosolic signals for the proliferation and growth of tumor cells in spite of being a “kinase dead” receptor that binds to its true ligand, heregulin. Although other members of the HER3 family like EGFR and HER2 have long been recognized to be associated with breast tumorigenesis and studied because of their predictive and prognostic value, the significance of HER3 as an irrefutable component of HER family signalosome is a relatively new development. The recent understanding of signals originating from the oncogenic partnership of HER3 with HER2 in the context of HER2 amplification/overexpression showed the critical clinical value for the treatment of HER2+BC. The downstream signaling cascade (included but not limited to the PI3K signaling) associated with signals originating from HER2:HER3 dimers play a vital role in the tumorigenesis, drug-resistance and tumor progression of HER2+BC. The upregulation of HER3 activity provides an alternate “escape route” via which tumor cells bypass either the inhibition of the HER family RTKs or the inhibition of the downstream PI3K-AKT-mTOR signaling pathway. By understanding the signaling that provides this “escape route” for these tumor cells treated with a targeted therapy (HER2 inhibitors or inhibitors of downstream PI3K-AKT-mTOR signaling pathway), we are just beginning to appreciate the prognostic value of HER3 in breast cancer. In this review, we will discuss the relevance of HER3 signaling in the context of, (1) downstream oncogenic signals and (2) therapeutic options in HER2 amplified BC.